Optimal Positioning for ERCP: Efficacy and Safety of ERCP in Prone versus Left Lateral Decubitus Position. (7th March 2013) - Batheja, Mashal; Harrison, M. Edwyn; Das, Ananya; Engel, Rodney; Crowell, Michael
Abstract : Background . ERCP is customarily performed with the patient in prone position. For patients intolerant of prone positioning, ERCP in left lateral decubitus (LLD) position offers a potential alternative. Aims . To compare efficacy and safety of ERCP in the LLD position versus prone position. Methods . Consecutive ERCP reports from August 2009 to October 2010 at Mayo Clinic Arizona were reviewed. Inclusion criteria . Age > 18 years, native papilla, and biliary indication. Primary outcome measure . Bile duct cannulation rate. Secondary outcomes . Times to ampullary localization and bile duct cannulation and complication rate. Results . ERCPs reviewed from 59 patients in two positions: 39 prone and 20 LLD. Cannulation Rate. 100% prone versus 90% in LLD (P = 0.11 ). Median (IRQ) times . (1) Ampullary localization: 90 sec (70–110) prone versus 100 sec (80–118) (P = 0.16 ); (2) bile duct cannulation: 140 sec (45–350) prone versus 165 sec (55–418) LLD (P = 0.54 ). Complications . No periprocedure; postprocedure 4 (10%) prone versus 3 (15%) LLD (P = 0.65 ). Conclusion . ERCP performed in LLD position allowed deep bile duct cannulation in 90% of patients without significantly increased procedural times or rate of complications as compared to prone position.